Biologically Synthesized Zinc Oxide Nanoparticles and Carbon Tetrachloride as an Anti Cancer Drug: A Review - Muhammad Haseeb Basharat, Muhammad Tariq, Riaz Mustafa, Amar Akash, Hafiza Hira Talib, Muhammad Nouman Aziz, Anadil Noel, Adnan Zeb, Muhammad Farooq Khalid, Fakhra Soomro, Qudsia Mushtaq, Mehreen Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Cancer is a life-threatening disease, curing it is one of the primary tasks for scientists around the world. One of the major fields that have exceptional abilities to control cancer is nanotechnology and nano medicines. Zinc oxide nanoparticles have flexible platforms for therapeutic and biomedical practice. There is a vital need to manufacture a new anti-cancerous drug. Zinc oxide nanoparticles have a great potential to act as an anti-cancerous drug. A common effect of zinc nanoparticle and carbon tetrachloride is the primary concern on the liver, biologically synthesized nanoparticles can be used for this cure purpose. This review study aims to explain the effects of synthesized nanoparticles on the rat in the presence of CCl4; Combination of toxic substance with the presence of nanoparticle can give us a better idea on the effectiveness of nanoparticle. Keywords: Zinc oxide nanoparticles, Liver cirrhosis, Carbon tetrachloride, Liver function